Does urbanization improve energy efficiency? Empirical evidence from China - Yu, Yantuan; Luo, Nengsheng (Technological and Economic Development of Economy, 2022)
An analysis of urbanization’s effects on energy efficiency (EE) is presented in this paper. We develop an input-oriented data envelopment analysis method to estimate EE in the presence of non-convex metafrontier, and examine how urbanization affects China’s EE using data from 251 cities for the period 2003 to 2016. The findings indicate that demographic urbanization (DU), land urbanization (LU), and economical urbanization (EU) significantly exert positive effects on EE. Specifically, estimates from a Tobit model with random effects show that a unit increase in DU, LU and EU would result in an increase in EE by 0.15, 0.15 and 0.45, respectively. These results are robust across econometric specifications, including fixed and correlated random effects Tobit models. Sensitivity analysis of quasi-DID and stochastic frontier estimations also support our findings. The policy implications suggest policymakers should steer urbanization and energy consumption towards becoming more market-oriented and take advantage of how energy market structure complements energy structure, cultivating new energy industries that can greatly improve EE. First published online 20 May 2022